2019
DOI: 10.1097/tp.0000000000002696
|View full text |Cite
|
Sign up to set email alerts
|

Trends, Determinants, and Impact on Survival of Post-Lung Transplant Weight Changes: A Single-center Longitudinal Retrospective Study

Abstract: Original Clinical Science-General Background. Weight gain is commonly seen in lung transplant (LTx) recipients. Although previous studies have focused on weight changes at fixed time periods and relatively early after transplant, trends over time and long-term weight evolution have not been described in this population. The study objectives were to document weight changes up to 15 years post-LTx and assess the predictors of post-LTx weight changes and their associations with mortality. Methods. Retrospective c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
(15 reference statements)
0
4
0
Order By: Relevance
“…Previously, we found that overweight LTx recipients lost weight in the early posttransplant period but regained weight between 1 and 2 y. 1 Although the magnitude of weight gain was below that of underweight and similar to normal-weight patients, it is probably enough to shift overweight patients into the obese category. The finding that COPD patients are at a higher risk of new-onset obesity raises questions regarding metabolic changes after transplantation.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Previously, we found that overweight LTx recipients lost weight in the early posttransplant period but regained weight between 1 and 2 y. 1 Although the magnitude of weight gain was below that of underweight and similar to normal-weight patients, it is probably enough to shift overweight patients into the obese category. The finding that COPD patients are at a higher risk of new-onset obesity raises questions regarding metabolic changes after transplantation.…”
Section: Discussionmentioning
confidence: 82%
“…New-onset obesity has been studied in other solidorgan transplants [14][15][16] but not extensively in the context of LTx. Previous studies showed that the prevalence of obesity increased from approximately 5% at transplant to 7% to 16% in the first 3 y after LTx 1,17,18 ; however, studies have not always clearly stated whether obesity was present before transplantation. We found that 13% of candidates had a BMI in the obese category, with 57% maintaining this status after transplantation.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The prevention of weight gain, overweight and obesity reduces the risk of CVD, diabetes and mortality among the general population 15,16 . Jomphe et al., 17 reported a lower median survival among LTx recipients with an unfavourable BMI evolution 2‐years post‐transplant, including those who became overweight or obese.…”
Section: Discussionmentioning
confidence: 99%